2019
DOI: 10.1590/1983-21252019v32n307rc
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Gains in the Popcorn Population Uenf-14: Developing the Ninth Generation of Intrapopulation Recurrent Selection

Abstract: The occurrence of negative correlations between grain yield (GY) and popping expansion (PE) in popcorn complicates the selection process. In an attempt to overcome this inconvenience, we proposed the use of the importance characteristic volume per popcorn per hectare (PV). The objectives of this study were to develop the ninth cycle of the UENF-14 popcorn population, to estimate the direct and indirect effects of PV and to verify the genetic progress among all selective cycles. We obtained and evaluated 200 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Adjustments of the set effects for all the hybrids were made according to the average of the controls common to all the sets before conducting the analysis of variance. We estimated the average of the controls for each set (ACS) and the general average of the controls (GAC); using the GAC/ACS relationship, the adjustment factor for each set was obtained, following the procedure used by Ribeiro et al [54] and Guimarães et al [55].…”
Section: Discussionmentioning
confidence: 99%
“…Adjustments of the set effects for all the hybrids were made according to the average of the controls common to all the sets before conducting the analysis of variance. We estimated the average of the controls for each set (ACS) and the general average of the controls (GAC); using the GAC/ACS relationship, the adjustment factor for each set was obtained, following the procedure used by Ribeiro et al [54] and Guimarães et al [55].…”
Section: Discussionmentioning
confidence: 99%
“…Two main breeding strategies are used to develop superior popcorn genotypes for registration and release as new cultivars, specifically recurrent selection and hybridization (Amaral Júnior et al, 2013;Guimarães et al, 2019). Recurrent selection increases the number of favorable alleles gradually, without altering the genetic variability of the population (Ribeiro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, when partitioning the genome, as in the RHM method, the values within each genomic window may be too low to be detected by the analysis. The same is not true for GY, for which the highest heritability values were recorded by RHM, and which, despite the strong environmental influence on it [ 66 , 67 ], has been shown to remain stable in successive cycles of intrapopulation recurrent selection in the population sampled here [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 82%
“…In the UENF-14 population intrapopulation recurrent selection program, it was observed that heritability remained stable in cycles 4, 5 and 6 (45.97%, 51.94%, and 45.04%, respectively) [ 70 ]. In addition, a heritability of 91% for GY was observed in cycle 9 of the same population [ 71 ]. In research carried out by Resende and collaborators [ 24 ], the estimated genomic heritability captured a relatively large proportion (72%) of the total heritability of the traits.…”
Section: Discussionmentioning
confidence: 99%